2022
DOI: 10.1021/acs.est.2c05396
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown and Modification of Microplastic Beads by Aeolian Abrasion

Abstract: Saltation is an important wind erosion process that can cause the modification and breakdown of particles by aeolian abrasion. It is recognized that microplastic particles can be transported by wind, but the effect of saltation on microplastic properties is unknown. This study examined the impact of simulated saltation alongside quartz grains on the size, shape, and surface properties of spherical microplastic beads. The diameter of the microplastics was reduced by 30–50% over 240–300 h of abrasion with a mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 56 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…Besides, there may be a greater variety of mechanical forces and the intensity of mechanical fragmentation may also be higher in terrestrial environment, such as erosion caused by rainwater 65 and tearing caused by strong winds. 66 However, these processes represent only the physical disintegration of commercial plastics into microplastics. Further in-depth and systematic research is needed in the future to study the time and factors influencing plastic mineralization in the terrestrial environment.…”
Section: Estimation Of Microplastics Released and Potentialmentioning
confidence: 99%
“…Besides, there may be a greater variety of mechanical forces and the intensity of mechanical fragmentation may also be higher in terrestrial environment, such as erosion caused by rainwater 65 and tearing caused by strong winds. 66 However, these processes represent only the physical disintegration of commercial plastics into microplastics. Further in-depth and systematic research is needed in the future to study the time and factors influencing plastic mineralization in the terrestrial environment.…”
Section: Estimation Of Microplastics Released and Potentialmentioning
confidence: 99%
“…Agricultural plastic film that has been exposed to UV radiation has been shown to easily break into debris (ultimately forming MNPs) when exposed to wind abrasion [74]. Bullard et al demonstrated that during wind abrasion (aeolian saltation), MPs can be fragmented, as shown by the reduction in the diameter and weight of the spherical MP beads [75].…”
Section: Mnps From Wind Abrasion and Erosionmentioning
confidence: 99%
“…The size distribution of MPs in emitted dust can be affected by processes such as saltation and creep. 20 Bullard et al 21 have investigated the fragmentation of MP beads by quartz particles due to saltation for different wind abrasion time periods. They found that MPs can lose 80% of their mass and some 50% of their diameter after 300 h of aeolian abrasion.…”
Section: Introductionmentioning
confidence: 99%